MODEL PEMBELAJARAN READING ROLLING TEXT DALAM PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Saebani . (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The success of learning History of Islamic Culture (SKI) can be influenced by many factors one of which is the method of learning. In fact the actual learning of SKI is not difficult, but many students who have less satisfactory learning outcomes in the lesson SKI. From this condition the authors try to use the Reading Rolling Text method (RRT) in the learning of SKI. The sample used in this study is the Class VIII Junior High School Students Al-Firdaus Mertoyudan Magelang District, which amounted to 25 students. Data analysis using descriptive analysis and parametric inferential statistical analysis with paired sample t test statistic. Test paired sample t test is a test conducted where the same sample but has two different data. The results of this study show that the use of RRT methods in SKI learning can improve learning outcomes.